Aprendendo sobre vacinas no Ensino Médio: uma proposta de sequência didática investigativa - Ana Regina de Melo Souza (2022)
The school is essential in the construction of scientific knowledge. Among the issues of great importance is the topic of vaccination. The spread of fake news and the lack of scientific knowledge on the subject has led part of the population to refuse vaccination. This work, therefore, aimed to build scientific knowledge about vaccination by high school students from a state public school in Belo Horizonte - MG. For this, an investigative didactic sequence was used, focusing on science, technology, society and environment (CTSA). The didactic sequence was divided into seven stages, in which the students reflected on the composition of vaccines and the care to handle them. They also simulated work plans for making vaccines. Then, they researched the characteristics of the immunizations against COVID-19 in use in Brazil and participated in a lecture with specialists in immunology and vaccines. Finally, they created an explanatory video to disseminate the knowledge obtained to the school community. The results showed greater student interest in the topic of vaccination, recognition of the scientific method, improvement in scientific learning and clarification of fake news, which contributed to increasing students' confidence in vaccines.